Moderne Nederlandse poëzie en de oorlogen in voormalig Joegoslavië - Novaković-Lopušina, Jelica (My University, 2011)
Recent Dutch and Flemish poetry shows many reactions and reflections on the bloody Yugoslav drama of the late twentieth century. The wars in former Yugoslavia were close to home. Also, the Dutch and Belgian military were involved in the events. Furthermore, the media played a crucial role by involving entire populations in the conflict as virtual eyewitnesses. Some poets rely on the poetics of fascination and disgust for violence as set out by the renowned Dutch poet Armando. Others prefer the almost silent mourning for the condition humaine. Some prefer implicit pacifist engagement, others express explicit political judgements. The dominant impression is the need of so many poets to react, reaffirming thus the belief in the strength of words as the only weapon of dignity.
Keywords: war poetry; modern Dutch and Flemish poetry; Yugoslavia